Argumentation Schemes for Stress Inference - Morales, Alison R. Panisson; Morales, Analúcia Schiaffino (Anais da Brazilian Conference on Intelligent Systems (BRACIS), 2025)
Stress arises from interactions between individuals and their environment, often exceeding coping resources and leading to severe consequences, especially in high-risk occupations like intensive care units (ICUs). This study reviews stress assessment models and proposes argumentation schemes for stress inference. Leveraging enthymematic reasoning, these schemes formalize patterns linking contextual, physiological, and psychological factors to stress attributions. Our approach enhances automated stress reasoning, supporting interventions in critical environments.